(untitled) (Il Risorgimento. Rivista di storia moderna e contemporanea, 2024)
Translation Policy and Methods of Legal Translation during the Napoleonic Period. This paper deals with the following aspects: The policies of translation during the French Revolution and the Napoleonic period in France, Belgium, Italy and Germany; typical profiles of legal translators during this period; the methods of legal translation (literal/foreignizing vs free/domesticating). The data are based on research projects financed by the Deutsche Forschungsgemeinschaft. According to the author of this article, the translation policy is not an ephemeral phase of the French revolution, but it concerns the whole era in consideration, until the end of the Napoleonic period. The dominant method of translation is (more or less) literal, with only some adaptations to the target language and culture.